Moving Histories: Discourses on Irish Women's Emigration to England Examined, 1922-1948 - Redmond, Jennifer (Trinity College Dublin, 2007)
This thesis looks at the public and private discourses on Irish women's emigration to England in the post-independence, pre-Republic era.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Migration -- women; Ireland, 1922-1948